Environmental policy and landscape architecture. - (:unkn) unknown (AVM, 2014)
The symposium focused on how the many different facets of landscape architecture could help towards solving environmental problems. Sustainable Development and Landscaping, Environmental Policy and the Contribution of Landscape Architecture at a Local Level, Designing Public Open Spaces and Social Sustainability, Spatial Planning and Landscape Architecture in Israel/Palestine, and Water and Soil: Crisis and Conservation are the key chapters in this volume. The authors address a wide range of issues including the significance of religions in ideas about environmentalism in historical and current debates, how Palestinian society can meet challenges posed by the dynamic development of urban structures through capacity building in landscape architecture, and economically meaningful strategies for soil conservation in arable fields as part of agricultural sustainability in semi-arid areas. A key objective of the symposium was also to determine opportunities for cooperation in the field of environment and landscaping for Israelis, Palestinians, Muslims, Jews and Christians in a region marked by huge tension and conflicts.
Keywords: Umweltschutz; Umweltpolitik; Landschaftsgestaltung; Landschaft; Natur; Agrarlandschaft; Stadtlandschaft; Landwirtschaft; Freifläche; Landschaftsarchitektur; Landnutzung; Nachhaltige Entwicklung